Making martyrs posthumous revolutionists; Chinese People’s Liberation Army’s policies for repatriating soldiers’ remains and accounting for the missing after the Chinese Civil War and the Korean War - Liu Zhaokun (Human Remains and Violence, 2023)
After the Chinese Civil War (1946–49), hundreds of thousands of graves of the People’s Liberation Army soldiers dotted the country’s landscape; the ensuing Korean War caused more casualties. Honouring this immense sacrifice and mobilising the survivors for its reconstruction were indispensable for the nascent People’s Republic of China. This research probes China’s policies to repatriate soldiers’ remains and account for those missing after these wars. The dilapidating status of soldiers’ graves threatened the morale of soldiers’ families, the backbone of the country’s socialist revolution. The state acknowledged families’ wishes to retrieve soldiers’ remains and nationalised their repatriation to salvage popular support. However, the deceased were not to drain the labour and resources reserved for the revolution. This principle had effectively prevented most families from retrieving remains. Accounting for missing soldiers was to ensure that only the revolutionary martyrs’ families could receive due honour and privilege.